The SLMTA programme: Transforming the laboratory landscape in developing countries - Katy Yao; Talkmore Maruta; Elizabeth T. Luman; John N. Nkengasong (AOSIS, 2014)
Background: Efficient and reliable laboratory services are essential to effective and well-functioning health systems. Laboratory managers play a critical role in ensuring the quality and timeliness of these services. However, few laboratory management programmes focus on the competencies required for the daily operations of a laboratory in resource-limited settings. This report provides a detailed description of an innovative laboratory management training tool called Strengthening Laboratory Management Toward Accreditation (SLMTA) and highlights some challenges, achievements and lessons learned during the first five years of implementation (2009-2013) in developing countries. Programme: SLMTA is a competency-based programme that uses a series of short courses and work-based learning projects to effect immediate and measurable laboratory improvement, while empowering laboratory managers to implement practical quality management systems to ensure better patient care. A SLMTA training programme spans from 12 to 18 months; after each workshop, participants implement improvement projects supported by regular supervisory visits or on-site mentoring. In order to assess strengths, weaknesses and progress made by the laboratory, audits are conducted using the World Health Organization's Regional Office for Africa (WHO AFRO) Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist, which is based on International Organization for Standardization (ISO) 15189 requirements. These internal audits are conducted at the beginning and end of the SLMTA training programme. Conclusion: Within five years, SLMTA had been implemented in 617 laboratories in 47 countries, transforming the laboratory landscape in developing countries. To our knowledge, SLMTA is the first programme that makes an explicit connection between the performance of specific management behaviours and routines and ISO 15189 requirements. Because of this close relationship, SLMTA is uniquely positioned to help laboratories seek accreditation to ISO 15189.